Meneropong Moderasi Beragama Dalam Kacamata John S. Dunne Mengenai Passing Over and Coming Back - Widyawan, Vincentius Happy Bayu; Joko Lelono, Martinus (Litbang STFT Widya Sasana Malang, 2024)
Abstract In 2016, the Ministry of Religious Affairs promoted the idea of religious moderation. This idea was put forward to overcome the threat of extremism, create a harmonious society and find a middle path in religious life. However, in its implementation, religious moderation remains open to the theoretical frameworks of different religions. Development of this idea must continue to develop a mature theoretical framework that can be understood and applied. To enrich this theoretical framework, religious moderation will be analyzed using John S. Dunne's thoughts on leaving and returning. The Passing Over and Coming Back method shows how people temporarily switch from their own perspective to someone else's, then return to a much more moderate perspective. This theory will be used to analyze the framework reflecting religious moderation proposed by the Ministry of Religious Affairs. Thus, through this article, we hope to enrich the theoretical framework of religious moderation and explore the contribution of John S. Dunne's thought to religious moderation. Abstrak Pada tahun 2016, Kementerian Agama menggaungkan ide mengenai Moderasi Beragama. Ide ini dimunculkan untuk mengatasi ancaman radikalisme, menciptakan masyarakat yang harmonis, dan menemukan jalan tengah dalam hidup beragama. Akan tetapi, dalam pelaksanaannya Moderasi Beragama masih terbuka terhadap kerangka teoritis dari berbagai agama. Pengembangan ide ini perlu untuk terus dilakukan agar memiliki kerangka teoritis yang matang, sehingga dapat dipahami dan diterapkan dengan baik. Untuk memperkaya kerangka teoritis tersebut, Moderasi Beragama akan akan dianalisis dengan pemikiran John S. Dunne mengenai passing over and coming back. Metode Passing Over and Coming Back berbicara mengenai bagaimana orang untuk sementara waktu berpindah dari sudut pandangnya sendiri ke sudut pandang orang lain dan kemudian kembali dengan sudut pandang yang jauh lebih moderat. Teori ini akan digunakan untuk menganalisis kerangka berpikir Moderasi Beragama yang ditawarkan oleh Kementerian Agama. Dengan demikian, melalui tulisan ini diharapkan dapat memperkaya kerangka teoritis Moderasi Beragama dan menemukan kontribusi pemikiran John S. Dunne terhadap Moderasi Beragama.